A Primary Study on Data Mining Tool Usage and Pattern Recognition in Retail CRM Systems - Ahire, Vrushali Yadavrao (International Journal of Engineering and Management Research, 2025)
In the rapidly evolving retail landscape, Customer Relationship Management (CRM) systems have become central to managing consumer interactions and fostering long-term loyalty. With the advent of big data, data mining tools have emerged as critical enablers of intelligent CRM, allowing businesses to extract meaningful patterns, predict customer behavior, and personalize engagement strategies. This study presents a primary investigation into the usage of data mining tools and pattern recognition techniques within retail CRM systems, focusing on their adoption, functionality, and effectiveness. Primary data was collected through a structured questionnaire targeting CRM and data analytics professionals across Indian retail organizations. The study explores the extent to which data mining tools such as association rule mining, clustering, and classification are utilized, and how these tools support segmentation, churn prediction, and sales forecasting. Findings suggest that while awareness and adoption of data mining in CRM are increasing, challenges remain in terms of tool integration, data quality, and skilled personnel. This research contributes valuable insights into the operational impact of data mining in enhancing CRM strategies and offers a framework for more effective retail data analytics implementation.